The origins, roles and therapies of cancer associated fibroblast in liver cancer - Zulaziz, Natasha; Chai, San Jiun; Lim, Kue Peng (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is the most common form of liver cancer. It is often preceded by chronic inflammation such as liver fibrosis and cirrhosis. Different cell types are believed to give rise to liver-specific cancer associated fibroblast (CAF), these include resident fibroblast, hepatic stellate cell, liver cancer cell, hepatic sinusoidal endothelial cell and mesenchymal stromal cell. The abundance of fibroblasts has contributed to the cancer progression, immune modulation and treatment resistance in HCC. In this review, we discussed the origins, subtypes and roles of cancer associated fibroblasts in HCC. Their specific roles in shaping the tumour microenvironment, facilitating cancer growth, and modulating different immune cell types to confer a permissive environment for cancer growth. CAF is now an attractive therapeutic target for cancer treatment, however specific therapeutic development in HCC is still lacking. Hence, we have included preclinical and clinical development of CAF-specific interventions for other cancer types in this review. However, most CAF-specific therapies have resulted in disappointing clinical outcomes, likely due to the difficulties in differentiating CAF from normal fibroblast. A thorough understanding of the characteristics and functionalities of CAF is warranted to further improve the therapeutic efficacy of anti-CAF therapies.